Afectación al derecho a la libertad de los sujetos procesados en segunda instancia por indebida aplicacion del artículo 450 del Código de Procedimiento Penal (2024)
The following research wants to provide the reader with the legal tools, based on decisions from the high courts of Colombia, to solve the problem about the citizens who are on detention, waiting for a decision of the juridical superior of the judge who solve their case on first instance, all this, looking to protect the indicted´s fundamental rights of freedom and a fair process.